Gas Hydrate, Methanogenic Calcite, And 13C-Depleted Bivalve Shells From A Mud Volcano Offshore Los Angeles, California - James R. Hein (International Marine Minerals Society, 2005)
Methane and hydrogen sulfide vent from a cold seep above a shallowly buried methane hydrate in a mud volcano located 24 km offshore of Los Angeles, California in 800 m water. Bivalves, authigenic calcite, and methane hydrate were recovered in a 2.1 m piston core. Aragonite shells of two bivalve species are unusually depleted in 13C (to -19? d13C), the most 13C-depleted shells of marine macrofauna yet discovered. Carbon isotopes for both living and dead specimens indicate that they used in part carbon derived from anaerobically oxidized methane (AOM) to construct their shells. Although the?d13C values are highly variable among specimens, most fall within the range -12 to -19?. This variability may be diagnostic for identifying cold-seep/hydrate systems in the geologic record. Authigenic calcite is abundant in the cores down to about 1.5 m subbottom, the methane hydrate horizon. The calcite is strongly depleted in 13C d13C = -46 to -58?) indicating that AOM was the main carbon source. Three sources of methane are likely: a geologic hydrocarbon reservoir, and biogenic and thermogenic degradation of organic matter in basin sediments. Oxygen isotopes indicate that most calcite formed out of isotopic equilibrium with ambient bottom-water, under the influence of gas hydrate dissociation and strong methane flux. High concentrations of Ag, Hg, Cd, Tl, and other elements in mud volcano sediment reflect leaching of basement rocks by fluids circulating along an underlying fault. Fossil (geologic) methane was likely transported with these fluids.